Dynamic coefficient β curve determination - Song Jun Hwang (International Journal of Architecture and Urbanism, 2024)
Here we describe the process for determining the parameters of the dynamic coefficient b curve of key significance in determining the magnitude of seismic action. In the process, one method for determining the exellent period of seismic waves is proposed and the design value of the dynamic coefficient curve, the function of the descent interval, the branch point, and especially the acceleration response spectrum in the case T=10 s.